Media Information Compared to Scientific Studies Regarding Piranha Attacks in Brazil - Gomes, Patrícia Tatiane [UNESP]; Rahal, Sheila Canevese [UNESP]; Fávero, Edson Luiz [UNESP]; Mendes, Adriana Lúcia [UNESP]; Martins, Itamar Alves; Haddad, Vidal [UNESP] (FapUNIFESP (SciELO), 2025)
BACKGROUND: Piranhas are carnivorous fish that inhabit rivers in Central and South America, and they are popularly recognized as relentless hunters of continental waters. Their reputation as killers is fueled by folklore and cinematographic works, which contribute to the creation of myths, generation of fear among people, and the vilification of fish. METHODS: We analyzed several media reports on piranha bites that occurred in Brazil, seeking to demystify these attacks as they are described in the lay press, using the injuries and circumstances observed as a basis. In addition, we highlighted human actions that directly affect piranha behavior. RESULTS: Of the 711 cases reported in humans in the last 10 years, 82.27% were classified as mild, with single "punch-out"-shaped injuries associated with the behavior of males to protect nests and larvae in dams and lakes. Seasonal analysis revealed that 29.62% of attacks occurred during the breeding season and 25.92% were associated with improper disposal of food in rivers. CONCLUSIONS: Media coverage of piranha attacks tends to negatively reinforce popular perceptions of the behavior of these species toward humans, diverting attention from human responsibility for the environmental impacts that directly influence the occurrence of these injuries.